A low power 10 V programmable array based on NbxSi1−x Josephson junctions for metrology applications. (10th August 2016) - Knipper, Richard; Anders, Solveig; Schubert, Marco; Peiselt, Katja; Scheller, Thomas; Franke, Dirk; Dellith, Jan; Meyer, Hans-Georg
Abstract: Josephson junctions generate, when subjected to microwave irradiation, voltages with a very high precision and are used in metrology applications. So-called PJVS (programmable Josephson voltage-standards) are capable of generating both AC and DC voltages of up to 10 V. Our work addresses a full fabrication scenario for 10 V PJVS arrays driven at 70 GHz to be used in low microwave-power conditions as in, but not limited to GUNN diodes or cryocooler applications. Nb x Si1− x in its function as a barrier material was characterised with AFM, RBS and reflectometry in order to establish a reliable technological foundation. A 10 V PJVS array driven with microwave power below 50 mW is further presented, which was achieved by optimising the fabrication technology regarding the degree of homogeneity of the Josephson junctions composition and thickness. Control over these parameters is crucial in choosing a stable and well-suited characteristic voltage ( I c R n  product) and critical current density j c . With this, a low-power operation of a PJVS array is possible without the need for liquid helium cooling, which is currently limiting the availability of PJVS based metrology.